Cone-Beam Computed Tomographic Evaluation of Radicular Grooves in Maxillary Anterior Teeth in a Selected Iranian Population - Ghahramani, Yasamin; Safarzade Haghighi, Bahare; Abbaszadegan, Abbas; Shahidi, Shole (Iranian Endodontic Journal, 2018)
Introduction: The region of maxillary anterior teeth is susceptible to numerous anomalies such as radicular groove (RG). RG usually begins by the cingulum of the tooth and proceeds to the root surface in various lengths and depths. This anomaly can prone the tooth to periodontal and endodontic pathosis. The aim of this study was to evaluate the prevalence of RG in maxillary anterior teeth in an Iranian population using cone-beam computed tomography (CBCT). Methods and Materials: A total of 552 CBCT images of maxillary anterior teeth were randomly selected from the archive of a radiology clinic in Shiraz, Iran. Eighteen hundred maxillary anterior teeth met the inclusion criteria. The variants including patient’s gender, tooth type, presence or absence and unilateral or bilateral incidence of RGs, their types, and mesiodistal location of RGs were analyzed using the Chi-square test. Results: RGs were diagnosed in 0.5% of central incisors, 2.6% in lateral incisors and 0.16% in canines. The prevalence of RGs in maxillary incisors and maxillary anterior teeth were calculated 1.58% and 1.11%. Statistical analysis showed that there was no significant relationship between gender and the presence, symmetry and location of RGs, but different tooth types had significant differences in the presence of RGs. Conclusion: In this cross sectional study the prevalence of RG had higher frequency in lateral incisors in comparison with canines and central incisors. CBCT is very useful in RG cases and is beneficial in RG diagnosis and treatment planning. Keywords: Cone-Beam Computed Tomography; Dental Anomalies; Radicular Groove